Comparing the Immersive Levels of Trivia Hidden Object Game Paper-based and Game Applications - Jahsy, Ibnu; Ilyas Nuryasin; Hardianto Wibowo (Bina Nusantara University, 2025)
The widespread development of the digital gaming industry in Indonesia began in 2000. The growth in interest in gaming has led to various objectives and encouraged research into several aspects and concepts of digital games. The aim of this research is to examine how significant the immersive differences are between paper-based game versions and applications/games among participants over 40 years old. The total average immersion obtained from the paper version is 4.43, while the application/game version is 5.85. For the average immersion per scale, the results of testing per scale show that the lowest average for the paper version is found in the Presence scale with 4.15, and the highest in Usability with 4.81. In the application/game version, the lowest average is found in the Focus Of Attention scale with a total of 5.55. The Usability scale scored 6.11, which is the highest result in the application/game version. The Interest scale is a category that has a significant difference between the paper and application/game versions with a margin of 1.6.